2012
DOI: 10.1097/olq.0b013e318255aeef
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Intraepithelial Neoplasia Is Associated With Genital Tract Mucosal Inflammation

Abstract: Background Clinical studies demonstrate increased prevalence of human papillomavirus (HPV)-associated disease in HIV-infected individuals and an increased risk of HIV acquisition in HPV-infected individuals. The mechanisms underlying this synergy are not defined. We hypothesize that women with cervical intraepithelial neoplasia (CIN) will exhibit changes in soluble mucosal immunity that may promote HPV persistence and facilitate HIV infection. Methods The concentrations of immune mediators and endogenous ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 30 publications
3
52
0
1
Order By: Relevance
“…These are secreted as pro-cytokines and are subsequently cleaved to form the smaller cytokine units of about 25 to 33 kDa depending on the exact product. Increased levels of IL-1 α/β and IL-10 were observed in cervicovaginal secretions of women with CIN, HPV and HIV indicating the adverse effect of Sexually transmitted infections on cytokine profile (Mhatre et al, 2012). Both IL-1 α/β act via IL-1RI and the polymorphism of IL-1 as well as its receptor are associated with risk of cancer.…”
Section: Il-1 α/βmentioning
confidence: 96%
See 1 more Smart Citation
“…These are secreted as pro-cytokines and are subsequently cleaved to form the smaller cytokine units of about 25 to 33 kDa depending on the exact product. Increased levels of IL-1 α/β and IL-10 were observed in cervicovaginal secretions of women with CIN, HPV and HIV indicating the adverse effect of Sexually transmitted infections on cytokine profile (Mhatre et al, 2012). Both IL-1 α/β act via IL-1RI and the polymorphism of IL-1 as well as its receptor are associated with risk of cancer.…”
Section: Il-1 α/βmentioning
confidence: 96%
“…However biopsy is an invasive procedure and is particularly non-desirable in the younger women desirous of conserving menstrual and childbearing functions. Hence further studies were carried out by authors who have observed that the higher local or circulatory peripheral concentrations of some cytokines are indicative of a higher risk of progression from CIN 1 to CIN 2 or 3 and further to invasive cancer and metastasis (Adam et al, 1999;Fugimoto et al, 2000;Pardo-Govea et al, 2005;Bais et al, 2007;Sharma et al, 2007;Hong et al, 2010;Kemp et al, 2010;Ali et al, 2012;Mhatre et al, 2012;Peghini et al, 2012;Lazarenko et al, 2014). Souza et al (2013) recently demonstrated higher serum concentrations of IL-17, mean-pg/ml: 22.50 in HSIL vs 12.20 in LSIL, and of IL-22, mean pg/ml 168.2 vs 61.48, p<0.05 respectively.…”
Section: Cytokines As Markers Of High Risk Of Progression Of Cin Gradesmentioning
confidence: 99%
“…The amounts of Th1-promoting cytokines (IFN-␥, TNF) and Th2-promoting cytokines (IL-6, IL-10) were inversely correlated in HPV-positive samples without dysplasia and CIN1, but these correlations decreased with progressive disease grades, suggesting a role for an impaired immune response in disease progression. Mhatre et al (24) reported that women with negative Papanicolaou test results secreted higher levels of anti-inflammatory markers (IL-1 receptor antagonist, ␤-defensins 1, 2, and 3) and lower levels of proinflammatory cytokines (IL-1␣/␤, CCL5, and CXCL8) than did women with CIN1 and CIN3. IL-1 receptor antagonist and ␤-defensins are normally increased with inflammation and infection (24), so this reciprocal modulation with proinflammatory cytokines suggests dysregulation of the normal cytokine-defensin network.…”
Section: Hpv Infection and Disease Progressionmentioning
confidence: 99%
“…Mhatre et al (24) reported that women with negative Papanicolaou test results secreted higher levels of anti-inflammatory markers (IL-1 receptor antagonist, ␤-defensins 1, 2, and 3) and lower levels of proinflammatory cytokines (IL-1␣/␤, CCL5, and CXCL8) than did women with CIN1 and CIN3. IL-1 receptor antagonist and ␤-defensins are normally increased with inflammation and infection (24), so this reciprocal modulation with proinflammatory cytokines suggests dysregulation of the normal cytokine-defensin network.…”
Section: Hpv Infection and Disease Progressionmentioning
confidence: 99%
“…Conversely strong and diffuse (so-called "block-positive" staining) p16 immunoreactivity strongly favours an interpretation of high grade CIN (CIN2 and CIN3). [1][2][3][4][5][6][7] Consensus recommendations from the Lower Anogenital Squamous Terminology (LAST) project from the College of American Pathologists and the American Society for Colposcopy and Cervical Pathology advise pathologists to consider using p16 IHC for equivocal lesions only; when the H&E morphologic differential diagnosis is between a high grade disease and either a high grade mimic, such as immature squamous metaplasia or low grade disease. They state that although the grade of CIN should be based on the H&E histomorphology of the lesion, if a biomarker such as p16 IHC is used, the results may override the original H&E interpretation.…”
Section: Introductionmentioning
confidence: 99%